The Efficacy of Frayer Model to Enhance Pharmaceutical Vocabulary Mastery - Kaloeti, Ade Kristianus (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to investigate the impact of the Frayer model of learning on pharmaceutical vocabulary. The research employs a quantitative approach utilizing a quasi-experimental design. From the population of 53 first-semester pharmacy students at Universitas Kristen Immanuel, a sample of 30 students. Data were collected through pre-tests and post-tests of essay questions test administered to both the experimental and control groups. Statistical analyses were conducted on the test results using SPSS version 22. This finding indicates a significant effect of the Frayer model on pharmaceutical vocabulary among first-semester pharmacy students. The N-Gain score for the experimental class was 65.9%, which was notably higher than the N-Gain score of 13.6% for the control class. These results suggest that the Frayer model is a more effective instructional method for enhancing vocabulary acquisition in pharmacy education compared to conventional teaching methods.